Răspuns :
a+3b+2c=4496
a=1624
[tex] \frac{1}{4}*c= \frac{1}{4}*b+29 [/tex]
aducem la acelasi numitor adica 4 si vom avea
c=b+116
inlocuim ce stim in suma si vom avea
1624+3b+2*(b+116)=4496
3b+2b+232=4496-1624
5b+232=2872
5b=2872-232
5b=2640
b=2640:5
b=528
c=528+116
c=644
a=1624
[tex] \frac{1}{4}*c= \frac{1}{4}*b+29 [/tex]
aducem la acelasi numitor adica 4 si vom avea
c=b+116
inlocuim ce stim in suma si vom avea
1624+3b+2*(b+116)=4496
3b+2b+232=4496-1624
5b+232=2872
5b=2872-232
5b=2640
b=2640:5
b=528
c=528+116
c=644
a=1624
1/4 *b =1/4 * c-29 |*4
b=c-116
a+3b+2c=4496
1624+3(c-116)+2c=4496
3c-348+2c=4496-1624
5c=2872+348
c=3220:5=644
b=c-116=644-116=528
1/4 *b =1/4 * c-29 |*4
b=c-116
a+3b+2c=4496
1624+3(c-116)+2c=4496
3c-348+2c=4496-1624
5c=2872+348
c=3220:5=644
b=c-116=644-116=528